Hubungan Antara Komunikasi Interpersonal Pasutri dengan Keharmonisan dalam Pernikahan - Dewi, Nyoman Riana; Sudhana, Hilda (Jurnal Psikologi Udayana, 2013)
Marital harmony will be difficult to achieve without a good interpersonal relationship between husband and wife. In creating a good interpersonal relationship needs effective communication so as to prevent yourself from situation that could damage the relationship and can lead to not harmonious marriage. This study aimed to determine the relationship between interpersonal communication with marital harmony.   This study is a quantitative research that used a product moment correlation. The sampling technique used is the technique simple random sampling , with 110 subjects. The scale used in this research are scale interpersonal communication and scale marital harmony. Based on the results obtained correlation values (r) of 0,649 with probabilities of 0,000 (p<0,05). The result from test data analysis is that there is a positive and significant correlation between interpersonal communication with marital harmony. The effective contribution to interpersonal communication with marital harmony is 42,2% and the others are 57,8% is influenced by other factors not examined in this study.   Keywords: Interpersonal communication, marriage harmony